2003
DOI: 10.1037/0022-0663.95.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Learning and transfer: A general role for analogical encoding.

Abstract: Teaching by examples and cases is widely used to promote learning, but it varies widely in its effectiveness. The authors test an adaptation to case-based learning that facilitates abstracting problemsolving schemas from examples and using them to solve further problems: analogical encoding, or learning by drawing a comparison across examples. In 3 studies, the authors examined schema abstraction and transfer among novices learning negotiation strategies. Experiment 1 showed a benefit for analogical learning r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
488
1
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 702 publications
(570 citation statements)
references
References 67 publications
22
488
1
23
Order By: Relevance
“…This finding agrees with the findings by Rittle-Johnson and Star (2007). The findings of the study also agree with prior cognitive science research on comparison as a basic learning methodology (Gentner, Loewenstein & Thompson, 2003;Namy & Gentner, 2002). It is also an indicator that this methodology can be used or employed to teach mathematics, especially algebra.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding agrees with the findings by Rittle-Johnson and Star (2007). The findings of the study also agree with prior cognitive science research on comparison as a basic learning methodology (Gentner, Loewenstein & Thompson, 2003;Namy & Gentner, 2002). It is also an indicator that this methodology can be used or employed to teach mathematics, especially algebra.…”
Section: Discussionsupporting
confidence: 91%
“…Case studies of expert mathematics teachers emphasise the importance of students actively comparing solution methods (Ball, 1993 . Gentner et al (2003) found that college students who were prompted to compare two business methods by reflecting on their similarities were much more likely to transfer the solution strategy to a new case than were the students who read and reflected on the cases independently. Thus identifying similarities and differences in multiple examples may be a critical and fundamental pathway to flexible, transferable knowledge.…”
Section: Introductionmentioning
confidence: 98%
“…There is, however, a robust literature in cognitive science that provides empirical support for the benefits of comparing contrasting examples for learning in other domains (mostly in laboratory settings; Gentner, Loewenstein, & Thompson, 2003;Kurtz, Miao, & Gentner, 2001;Loewenstein & Gentner, 2001;Namy & Gentner, 2002;Oakes & Ribar, 2005;Schwartz & Bransford, 1998). For example, college students who were prompted to compare two business cases by reflecting on their similarities were much more likely to transfer the solution strategy to a new case than were students who read and reflected on the cases independently (Gentner et al, 2003).…”
Section: Comparing Alternative Solution Methodsmentioning
confidence: 99%
“…For example, college students who were prompted to compare two business cases by reflecting on their similarities were much more likely to transfer the solution strategy to a new case than were students who read and reflected on the cases independently (Gentner et al, 2003). Thus, identifying similarities and differences in multiple examples may be a critical and fundamental pathway to flexible, transferable knowledge.…”
Section: Comparing Alternative Solution Methodsmentioning
confidence: 99%
“…Much of this research aims to lessen the challenges that students face when presented with the task of drawing comparisons between similar objects from markedly different contexts (Brophy & Schwartz, 1998;Medin, Goldstone, & Gentner, 1993) and when students have little domain expertise. Other research compared the effects of students being exposed to different representations, multiple examples, multiple questions, different levels of solution, and/or problem specificity, and the principles that underlie a given example (Colhoun, Gentner, & Loewenstein, 2008;Gentner, 2004;Gentner, Loewenstein, & Thompson, 2003;Loewenstein, 2010). Loewenstein (2010) deconstructs these different solution and problem formulations as being related to the ambiguity and context specificity, completeness, and featuring weighting.…”
Section: Analogical Problem Solvingmentioning
confidence: 99%